Non‐clinical safety evaluation of single and repeated intramuscular administrations of MAGE‐A3 Cancer Immunotherapeutic in rabbits and cynomolgus monkeys. Issue 7 (12th September 2014) - Destexhe, Eric; Grosdidier, Emilie; Baudson, Nathalie; Forster, Roy; Gerard, Catherine; Garçon, Nathalie; Segal, Lawrence
Abstract The MAGE‐A3 recombinant protein combined with AS15 immunostimulant (MAGE‐A3 Cancer Immunotherapeutic) is under development by GlaxoSmithKline for the treatment of lung cancer and melanoma. We performed non‐clinical safety studies evaluating potential local and systemic toxic effects induced by MAGE‐A3 Cancer Immunotherapeutic in rabbits (study 1) and cynomolgus monkeys (study 2). Animals were allocated to two groups to receive a single (rabbits) or 25 repeated (every 2 weeks) injections (monkeys) of MAGE‐A3 Cancer Immunotherapeutic (treatment groups) or saline (control groups). All rabbits were sacrificed 3 days post‐injection and monkeys 3 days following last injection (3/5 per gender per group) or after a 3‐month treatment‐free period (2/5 per gender per group). Local and systemic reactions and MAGE‐A3‐specific immune responses (monkeys) were assessed. Macroscopic and microscopic (for rabbits, injection site only) post‐mortem examinations were performed on all animals. No systemic toxicity or unscheduled mortalities were recorded. Single (rabbits) and repeated (monkeys; up to four times at the same site) injections were well tolerated. Following five to seven repeated injections, limb circumferences increased up to 26% (5 h post‐injection), but returned to normal after 1–8 days. Three days after the last injection, enlargements of iliac, popliteal, axillary and inguinal lymph nodes, and increased incidence or severity of mononuclear inflammatory cell infiltrates was observed in injected muscles of treated monkeys. No treatment‐related macroscopic findings were recorded after the treatment‐free period. MAGE‐A3‐specific antibody and T‐cell responses were raised in all treated monkeys, confirming test item exposure. Single or repeated intramuscular injections of MAGE‐A3 Cancer Immunotherapeutic were well tolerated in rabbits and monkeys. Copyright © 2014 GlaxoSmithKline Vaccines. Journal of Applied Toxicology published by John Wiley & Sons, Ltd.